Diseases - Bunch, Bryan H.; Grolier Educational (Firm) (Danbury, CT : Grolier Educational, 1997)
Alphabetically arranged articles present medical information on more than 400 diseases, discussing sources, symptoms, stages of the disease, its likelihood of striking, treatments, prevention, and long-term effects.
v. 1. Abscess to bone diseases -- v. 2. Bones to dermatitis -- v. 3. Detached retina to gallstones -- v. 4. Gangrene to infantile paralysis -- v. 5. Infants and disease to multiple sclerosis -- v. 6. Mumps to polyps -- v. 7. Porphyrias to spasm -- v. 8. Spider bites to zoonoses.
Includes index.
Keywords: Diseases -- Encyclopedias, Juvenile